A SIM-MOF: Three-Dimensional Organisation of Single-Ion Magnets with Anion-Exchange Capabilities - Baldoví, José J.; Coronado, Eugenio; Gaita-Ariño, Alejandro; Gamer, Christoph; Giménez-Marqués, Mónica; Mínguez Espallargas, Guillermo (Chemistry : a European journal, 2014)
The formation of a metal–organic framework (MOF) with nodes that have single‐molecule magnet (SMM) behaviour has been achieved by using mononuclear lanthanoid analogues, also known as single‐ion magnets (SIMs), which enormously simplifies the challenging issue of making SMM‐MOFs. Here we present a rational design of a family of MOFs, [Ln(bipyNO)4](TfO)3⋅x solvent (Ln=Tb (1); Dy (2); Ho (3); Er (4); TfO=triflate), in which the lanthanoid centres have an square‐antiprismatic coordination environment suitable for SIM behaviour. Magnetic measurements confirm the existence of slow magnetic relaxation typical of SMMs, which has been rationalised by means of a radial effective charge model. In addition, we have explored the incorporation of bulky polyoxometalates (POMs) into the cavities of the SIM‐MOF by anion exchange, finding that they do not interfere with the slow magnetic relaxation. This demonstrates the robustness of the frameworks and opens the possibility of incorporating non‐innocent anions. SIMs to be in (3D) order: The formation of a single‐ion magnet/metal–organic framework (SIM‐MOF) is presented, which enormously simplifies the challenging issue of making SMM‐MOFs. The incorporation of bulky polyoxometalates (POMs) into the cavities does not interfere with the slow magnetic relaxation, demonstrating the robustness of the frameworks and opening the possibility of incorporating non‐innocent anions.